IMPLEMENTASI SISTEM STREAMING SEBAGAI UPAYA PEMANTAUAN DAN PENUNJANG KESELAMATAN PROSES SANDAR KAPAL PADA PELABUHAN PINTAR - Aditya Firmansyach; Henna Nurdiansari; Wulan Marlia Sandi (UNIMAR AMNI Semarang, 2026)
This study aims to implement a real-time streaming system as a monitoring tool during the ship berthing process at a smart port, analyze the effectiveness of the streaming system in improving the monitoring and safety of the ship berthing process at a smart port, and explain how the components work in real-time to support the ship berthing process at a smart port. The ship berthing process is a crucial stage in port operations that requires real-time monitoring to ensure safety and efficiency. The developed system uses a Raspberry Pi as the main controller integrated with a V2 camera module, a proximity sensor, a WiFi hotspot module, and an Internet of Things (IoT)-based power monitoring system. Visual data in the form of streaming video and sensor data are sent in real-time to the monitoring application to assist port operators in monitoring the distance of ships to the dock. The research method used is Research and Development (R&D) which includes the design, assembly, testing, and evaluation stages of the system. Test results show that the system performs well in displaying real-time video streaming with an average streaming delay of 1.54%, accurately detecting vessel distances with an average of 0.81%, and providing relevant supporting information to improve the safety of ship berthing processes. Therefore, this system has the potential to be a supporting solution in the development of a safe and efficient smart port concept. Keywords: Internet of Things (IoT), Smart Port, Raspberry Pi, Straming System